Drought-tolerant lines of Physalis angulata L. improved growth, yield, and water use efficiency in drylands - Wiwin Sumiya Dwi Yamika; Nevy Kusuma Dewi; Budi Waluyo; Nurul Aini; Husni Thamrin Sebayang (Journal of Degraded and Mining Lands Management, 2023)
Cutleaf groundcherry (Physalis angulata L.) has the potential to be developed in various areas, including dryland. Information on drought-tolerant varieties, lines, or genotypes is needed for the development of cutleaf groundcherry in dryland. Selecting drought-tolerant lines is an alternative for alleviating yield loss potency caused by water shortages. A pot experiment that aimed to investigate the response of cutleaf groundcherry lines to a different level of water deficit, expressed in field capacity (FC), was run in two factors of factorial randomized block design. Each line (PA-01, PA-03, PA-05, PA-08) was set up in water deficit treatment (100, 80, 60, 40, and 20% FC). The result showed that vegetative growth and fruit production, such as fruit number and weight, mainly decreased at 60 or 40 % FC. In contrast, TSS increased at a higher water deficit which was in line with total flavonoid content, even inconsistently. PA-03 and PA-08 experienced a reduction in fruit weight at 40% FC, whereas other lines occurred at 60% FC. Water use efficiency (WUE) increased under severe water stress. Compared to other lines, PA-03 and PA-08 exhibit higher WUE at 60% FC. In conclusion, PA-03 and PA-08 lines were tolerant of water deficit.